Opto-magnetic imaging spectroscopy in characterization of the tissues during hyperbaric oxygen therapy - Sedlar, Mariana; Nikolić, Gorana V; Dragičević, Aleksandra; Koruga, Djuro (Vojnosanitetski pregled, 2015)
Background/Aim. Opto-magnetic imaging spectroscopy (OMIS) was used as a novel method to determine tissue molecular conformation changes during hyperbaric oxygen (HBO) therapy. The aim of this study was to examine the usefulness of OMIS for the assessment of HBO therapy effectiveness on the diseased tissue. Methods. OMIS is concerned with obtaining paramagnetic/diamagnetic properties of materials, related to the presence of unpaired/paired electrons based on their interaction with visible light. The basic tool is light of wavelength in the range between 400 nm and 700 nm and its interaction with tissue. The study included 22 subjects: 16 angiopathy patients and 6 healthy subjects as the control group. OMIS was used with patients on the 1st, 10th and 20th session and with the control group on the 1st, 10th and 20th day without HBO therapy in between. Results. The obtained results showed that healthy skin of all the control group subjects had the same shape curve. In the angiopathy patient group, before the first session OMIS showed tissue disorder and after the last session results resembled more closely the results in healthy tissue. The differences in the tissue state in the angiopathy group before each session were noticeable, showing normalized tissue under the influence of HBO. Conclusion. The results show that OMIS could be used as a diagnostic tool for detection of the tissue state before and after the HBO therapy.